2022
DOI: 10.1007/s10278-022-00619-6
|View full text |Cite
|
Sign up to set email alerts
|

What Influences the Way Radiologists Express Themselves in Their Reports? A Quantitative Assessment Using Natural Language Processing

Abstract: Although using standardized reports is encouraged, most emergency radiological reports in France remain in free-text format that can be mined with natural language processing for epidemiological purposes, activity monitoring or data collection. These reports are obtained under various on-call conditions by radiologists with various backgrounds. Our aim was to investigate what influences the radiologists’ written expressions. To do so, this retrospective multicentric study included 30,227 emergency radiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…While substantial variability in the use of uncertainty terms was observed, the degree of variability could not be explained by differences in years of experience of radiologists. Similar results were observed by Crombe et al [ 32 ] in a multicenter study of over 30,000 computed topography scans and magnetic resonance imaging interpreted by 165 radiologists. Despite having a smaller sample size, our study mirrors the findings of these studies in demonstrating no correlation between the use of uncertain language on imaging reports and the experience of the interpreting radiologist.…”
Section: Discussionsupporting
confidence: 90%
“…While substantial variability in the use of uncertainty terms was observed, the degree of variability could not be explained by differences in years of experience of radiologists. Similar results were observed by Crombe et al [ 32 ] in a multicenter study of over 30,000 computed topography scans and magnetic resonance imaging interpreted by 165 radiologists. Despite having a smaller sample size, our study mirrors the findings of these studies in demonstrating no correlation between the use of uncertain language on imaging reports and the experience of the interpreting radiologist.…”
Section: Discussionsupporting
confidence: 90%
“…Using natural language processing (NLP) to label reports could help generate large cohorts, plan human and technical resources, assess compliance with guidelines, and detect discrepancies between results and conclusions [ 1 3 ]. It has been recently shown that the structure and content of reports developed by emergency radiologists depend on their personal background, examination characteristics, or workload [ 4 ]. On a clinical side, one could hypothesize that an emerging new disease with significant impact on health would lead to new patterns of radiological depictions that could be captured with NLP before the semiology of the disease has been deciphered, which is inherently shifted by several weeks due to the time needed to understand patterns, collect databases, and statistically verify associations between features and diseases.…”
Section: Introductionmentioning
confidence: 99%